PENGARUH MODEL PEMBELAJARAN PJBL DAN MINAT BELAJAR TERHADAP HASIL BELAJAR MURID MATERI CERITA TENTANG DAERAHKU DI SD NEGERI 1 KUWARASAN - Kurniasih, Imas; Nur Ngazizah; Rintis Rizkia Pangestika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to: 1) Determine the influence of the PjBL learning model on student learning outcomes, 2) Determine the influence of learning interest on student learning outcomes, 3) Determine the influence of the PjBL learning model and learning interest on student learning outcomes. The research method used is Quasi Experimental with a Nonequvalent Control Group Design research design, and uses an experimental class and a control class. This research uses questionnaires and tests as the main tools for collecting data. Determining the number of samples in this research uses a sampling technique, namely census or total sampling, where the entire population is used as the research sample. The data processing techniques used are validity testing, homogeneity testing, difficulty testing, prerequisite testing, and hypothesis testing. The results of the research show that there is an influence between the PjBL learning model on learning outcomes, there is an influence between interest in learning on learning outcomes, and there is an influence between the PjBL learning model and interest in learning on student learning outcomes in the Story About My Region material. This is shown by a significance value below 0.05, so there is a positive relationship between these variables.